MEDIA PROMOTION OF RELIGIOUS TOURISM TOMB SYEKH MANSYURUDDIN CIKADUEN - Yuliah, Yuliah; Syapoetra, M. Syulaeman; Nugroho, Arif; Triana, Leni (Nindikayla Institute, 2024)
Tourism is an industry where if worked on optimally, will provide benefits both for the local government or the people who live around the tourism place and religious tourism in Banten Province, one of which is the Tomb of Sheikh Manshuruddin. The number of visitors to Sheikh Mansyuruddin's Tomb still tends to be slight compared to visitors to Eat in Banten Lama. This is due to the lack of promotional efforts, so that there are still many local people themselves who do not know the existence of Sykeh Mansyuruddin Tomb. From that, it is necessary to develop promotional media that can provide the right and exciting information to the audience to attract the public's interest to visit Sheikh Mansyuruddin's Meal and will have a positive impact on improving the economy of the surrounding community. The promotional media carried out by the community service team is to create a Website and also plang